The Relationship between Macro Nutrition And Physical Activities With Nutrition Status in Employee Offices of the Directorate Poltekkes Kemenkes Jakarta II - Novita Dewi; Isti Istianah (SANITAS: Jurnal Teknologi dan Seni Kesehatan, 2018)
Nutritional status was an important element in determining someone health status. Nutrition status was good when nutritional intake balanced with the needs of the Body. Physical activity was a way to regulate the amount of energy entering and leaving in the body. The purpose of this study was to analyze the relationship between the macronutrient intake and physical activity with nutritional status at office staff of Directorate Poltekkes Kemenkes of Jakarta II. This research was conducted in April-May 2018 at the Office of Poltekkes Kemenkes Directorate of Jakarta II. The number of samples which was obtained was 49 people and Cross-sectional research design with a Chi-Square test. The data which was used was primary data. It mean the researcher took the data by conducting direct interview with using questionnaire. Most intake of more protein as many as 27 people (55.1%), fat as many as 35 people (71.4%), and carbohydrates as many as 29 people (59.2%). More nutritional status as many as 32 people (65.3%) and normal nutritional status of 17 people (34.7%). While physical activity mostly has physical activity is as much as 34 people (69.45%). There was a significant relationship between protein intake (p: 0.042), fat intake (p: 0.000), carbohydrate intake (p: 0.000) with nutritional status. There was a relationship between the intakes of macronutrients (protein, fat and carbohydrates) with nutritional status